Modeling and Simulation of a Solar Power Source for a Clean Energy without Pollution - Mohamed Louzazni; El Hassan Aroudam; Hanane Yatimi (Institute of Advanced Engineering and Science, 2013)
Photovoltaic cell generation is the technique which uses photovoltaic cell to convert solar energy into electrical energy. Now a days ,the photovoltaic generation is developing increasingly fast as a renewable energy source. The functioning of a photovoltaic cell as the power generator is equivalent to an electric circuit containing a current generator, diode, series resistance and shunt resistance. This paper presents a modeling and simulation of a photovoltaic system constitutes of a generator (PVG), DC-DC converter (boost chopper) to transfer the maximum power to a base transmitter station. The temperature and irradiance effects on the PVG will be studied, particularly on the variables such as the short circuit current Icc, the open circuit voltage Voc, the performance η and the fill factor FF. Depending on the load (BTS, I=60A, V=48V) profile and climatic factors influencing, we can find a highly gap between the maximum power supplied by the PVG and that actually transferred to the BTS. A maximum power point tracker (MPPT) based on a boost converter commanded by a Pulse Width Modulation (PWM) is used for extracting the maximum power from the PVG. Thus, a real time tracking of the optimal point of functioning (MPP: Maximum Power Point) is necessary to optimize the efficiency on the system. The modeling and simulation of the system (PVG, boost converter, PWM and MPPT algorithm Perturbation and Observation P&O) is then made with Matlab/Simulink software.DOI:http://dx.doi.org/10.11591/ijece.v3i5.3639